Effects of vitamin D supplementation on symptoms and clinical outcomes in adults with different baseline vitamin D levels: an interventional study - Osama Albasheer; Siddig Ibrahim Abdelwahab; Ahmad Alqassim; Hatim Alessa; Afnan Madkhali; Afaf Hakami; Jamal Mohieddin; Anas E. Ahmed; Suhaila Ali; Amani Abdelmola; Omar Oraibi; Amal. H. Mohamed; et al. (Journal of Health, Population and Nutrition)
Abstract Background Hypovitaminosis D or vitamin D deficiency is a significant public health issue. Several vitamin D preparations are currently available. However, there is no consensus on the optimal dose and duration of vitamin D supplementation. This study aimed to evaluate the effects of vitamin D supplementation on symptoms and clinical outcomes in adults with insufficient or deficient baseline vitamin D levels. Method A pre-post two-month intervention with 50,000 IU vitamin D3 supplementation for adults with documented insufficient or deficient baseline vitamin D levels, presented at Jazan University Hospital from August to December 2022. Results Of the 204 participants, 65.1% had baseline vitamin D levels < 30 nmol/L. Vitamin D insufficiency is more prevalent among females, older adults, married individuals, and those with low income. However, these differences were not statistically significant (p > 0.5). The symptoms and clinical outcomes were significantly improved after 2 months of vitamin D3 supplementation for the participants who achieved vitamin D levels > 50 nmol/L (p = 0.000). After adjusting for multiple confounders, the significant determinants of symptom improvement and clinical outcomes post-supplementation included education level, income, smoking status, and baseline vitamin D level. Conclusions Hypovitaminosis D or vitamin D deficiency was observed in study participants. The use of a 50,000 IU cholecalciferol (vitamin D3) orally once per week for two months is sufficient to improve the symptoms and clinical outcomes of vitamin D deficiency. However, long-term follow-up could better assess the sustainability of benefits and explore long-term outcomes, such as the risk of deficiency recurrence. Clinical trial number Not applicable